SKIN TARGETING OF AN OPTIMIZED CAFFEINE NANOSTRUCTURED LIPID CARRIER WITH IMPROVED EFFICIENCY AGAINST CHEMOTHERAPY INDUCED ALOPECIA - MAKKY, AMNA MOHAMED; EL-LEITHY, EMAN SADDAR; HUSSEIN, DOAA GALAA; KHATTAB, ABEER (International Journal of Applied Pharmaceutics, 2022)
Objective: The current investigation was designed to develop and optimize caffeine-loaded nanostructured lipid carriers (NLCs) for topical alopecia treatment. Methods: Screening of drug solubility in various excipients was executed. The 23 full factorial design was employed for NLCs optimization. Lipid type, surfactant type, and drug concentration were the independent variables. Entrapment efficiency (EE), particle size, polydispersity index (PDI) and % drug release were the chosen responses. Physiochemical evaluation, in vitro release, ex-vivo permeation, and stability study were achieved. Results: The solubility of caffeine in stearic acid and glyceryl monostearate (GMS) was 47.11±3.048 and 32.67±2.955 mg/g, respectively. Oleic acid: garlic oil mixture at a ratio of 1:1 v/v was the oily phase. Tween 80 and Cremophor EL, Transcutol HP, carbonate buffer (pH 10.8 and ionic strength 200 mmol) were chosen as a surfactant, co-surfactant, and aqueous phase, respectively. The optimized formula showed particle size, %EE, PDI, zeta potential of 358 nm±1.45, 72.55 %±0.12, 0.912±0.030,-24.8 mv±0.70, respectively. The % release was 92.9±4.9 % after 2 h. Confocal laser scanning microscopy showed an improved permeation of caffeine-loaded NLCs to the whole skin layers. Conclusion: The histological examination proved the efficiency of caffeine NLCs optimized formula in promoting hair growth compared to the market formula.